1996
DOI: 10.1105/tpc.8.1.43
|View full text |Cite
|
Sign up to set email alerts
|

A soluble protein is imported into Euglena chloroplasts as a membrane-bound precursor.

Abstract: The Euglena precursor to the small subunit of ribulose-1,Bbisphosphate carboxylase/oxygenase (pSSU) is a polyprotein. To determine the transport route from cytoplasm to chloroplast, Euglena was pulse labeled with 35S-sulfate and the organelles were separated on sucrose gradients. After a pulse, pSSU was found in the endoplasmic reticulum (ER) and Golgi apparatus. During a chase, ER-and Golgi-localized pSSU decreased concomitant with the appearance of SSU in chloroplasts. SSU was not found in pSSU-containing ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 30 publications
1
39
0
Order By: Relevance
“…Details of the mechanism differ, however, as in Euglena the plastid-directed leader sequences contain two hydrophobic regions separated by an S/T-rich region reminiscent of a plastid transit sequence (Henze et al, 1995;Kishore et al, 1993). In vitro studies have demonstrated that the plastid directed proteins remain inserted in the ER membranes, unlike the apicomplexans where the plastid proteins are soluble inside the ER (Kishore et al, 1993;Osafune et al, 1990;Sulli et al, 1999;Sulli and Schwartzbach, 1996). The second hydrophobic region present in the Euglena leaders is absent in apicomplexan leaders (Foth et al, 2003).…”
mentioning
confidence: 99%
“…Details of the mechanism differ, however, as in Euglena the plastid-directed leader sequences contain two hydrophobic regions separated by an S/T-rich region reminiscent of a plastid transit sequence (Henze et al, 1995;Kishore et al, 1993). In vitro studies have demonstrated that the plastid directed proteins remain inserted in the ER membranes, unlike the apicomplexans where the plastid proteins are soluble inside the ER (Kishore et al, 1993;Osafune et al, 1990;Sulli et al, 1999;Sulli and Schwartzbach, 1996). The second hydrophobic region present in the Euglena leaders is absent in apicomplexan leaders (Foth et al, 2003).…”
mentioning
confidence: 99%
“…Marker enzymes identified fractions 2-5 as containing ER membranes, fractions 6-14 as containing light and dense Golgi membranes and fractions 14-22 as containing broken and intact chloroplasts (Sulli and Schwartzbach, 1995;Sulli and Schwartzbach, 1996). For direct comparisons between gradients loaded with differing amounts of 35 S-labeled protein, pLHCPII and LHCPII amounts in each fraction were plotted as the percentage of total immunoprecipitate (pLHCPII and LHCPII) recovered from the gradient.…”
Section: Euglena Golgi To Chloroplast Transport Is Reversibly Blockedmentioning
confidence: 99%
“…Immunoelectron microscopy localized Euglena and dinoflagellate chloroplast proteins to the Golgi apparatus (Nassoury et al, 2003;Osafune et al, 1991). In vivo pulse-chase immunoprecipitation experiments have shown that Euglena chloroplast precursors are transported in vesicles as integral membrane proteins from the ER to the Golgi apparatus prior to chloroplast localization (Sulli and Schwartzbach, 1995;Sulli and Schwartzbach, 1996). In vitro studies with canine microsomes have shown that the Euglena (Sulli et al, 1999) and dinoflagellate (Nassoury et al, 2003) pre-sequence signal peptide co-translationally inserts the precursor into the ER whereas the hydrophobic domain within the transit peptide region functions as a stop-transfer sequence anchoring the protein in the membrane oriented with the N-terminus formed by signal peptidase cleavage in the lumen and the remainder of the precursor in the cytoplasm.…”
mentioning
confidence: 99%
See 2 more Smart Citations